2019
DOI: 10.1186/s13014-019-1274-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of portal image resolution improvement using an external aluminum target and polystyrene electron filter

Abstract: Background In this study, an external 8 mm thick aluminum target was installed on the upper accessory tray mount of a medical linear accelerator head. The purpose of this study was to determine the effects of the external aluminum target beam (Al-target beam) on the portal image quality by analyzing the spatial and contrast resolutions. In addition, the image resolutions with the Al-target beams were compared with those of conventional 6 megavoltage (MV) images. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…MTF is regularly employed to assess a system's spatial resolution properties as well as the signal transfer accuracy through the imaging chain of a system. In the present study, MTF was expressed by the Coltman's formula [ 5 , 10 , 18 , 21 , 27 , 28 , [30] , [31] , [32] ]: where CTF is the Contrast Transfer Function defined by Refs. [ 18 , 21 , 28 ]: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MTF is regularly employed to assess a system's spatial resolution properties as well as the signal transfer accuracy through the imaging chain of a system. In the present study, MTF was expressed by the Coltman's formula [ 5 , 10 , 18 , 21 , 27 , 28 , [30] , [31] , [32] ]: where CTF is the Contrast Transfer Function defined by Refs. [ 18 , 21 , 28 ]: …”
Section: Methodsmentioning
confidence: 99%
“…Studies, e.g. investigating various issues such as the effects of external aluminum target beam of the LINAC on EPID [ 10 ], the use of wavelet analysis to detect and isolate defective pixels and artifacts for quantitative quality assurance (QA) of EPIDs, characterizing the image noise, have been published [ 6 ]. In addition, a review is referred to the properties of dosimetry and imaging of radiation detectors, such as the physical principles of operation of calorimeters ionization, charge detectors, semiconductor, luminescent, chemical detectors, and radiochromic films [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, Baek et al . showed that a gantry mounted aluminum target improved the limiting spatial frequency (f50) from 0.451 lp/mm to 0.745 lp/mm for a tungsten target 6 MV beam 8 . Additionally, Parsons et al .…”
Section: Introductionmentioning
confidence: 98%
“…6,7 Experimentally, Baek et al showed that a gantry mounted aluminum target improved the limiting spatial frequency (f50) from 0.451 lp/mm to 0.745 lp/mm for a tungsten target 6 MV beam. 8 Additionally, Parsons et al showed an increase in the contrast to noise ratio (CNR) in projection images of cortical bone by factors ranging from 3.7 to 7.4 between carbon and aluminum targets with 2.35 and 1.9 MV photon beams and the default 6 MV tungsten imaging setup. 9 Furthermore, advances in MV EPID design have shown promise in improving MV image quality.…”
Section: Introductionmentioning
confidence: 99%